10 - NGOs and Conflict Prevention in Burundi: A Case Study: DOI: 10.4314/ad.v30i1.22219 - Wohlgemuth, Lennart (Africa Development, 2005)
Since the abortive coup in October 1993, Burundi has been in a severe crisis, however, lately reaching a more hopeful situation. The international community has made substantial efforts at preventing the escalation of the conflict and at contributing to a process for sustainable peace in the country. This includes the UN system, bilateral countries and in particular the neighbouring states. A number of NGOs have been among the actors. Here the efforts of some major NGOs lending their support to Burundi's peace process are discussed both as regards their support for peace building and for support to peace mediation. The aim has been to assess their performance based on their aims and objectives in relation to respective NGO's overall reasons for coming to Burundi in the first place, as well as their wider aims. Efforts are made to find common denominators and possible conclusions and recommendations useful for others involved in similar activities in Burundi and elsewhere.